Survey on Image Compression Techniques - Kamalin, C. Jenifer; Lakshmi, G. Muthu (International Journal of Computer Sciences and Engineering, 2025)
The goal of this paper is to survey about various image compression techniques. Image compression is a very important to implement in digital image processing. It is the case of converting an image file in such a way that it consumes smaller space than the original file. Compression technique that reduces the size of an image file without disturbing or degrading its quality to a greater extent. The main intention of the compression is to minimize the amount or unnecessary data.The goal behind is to save the amount of memory required to save the images or to make practical network bandwidth in efficient manner.